Differentiating effect of thalidomide and GM-CSF combination on HL-60 acute promyelocytic leukemia cells - Ural, A.U.; Avcu, F.; Zerman, M.; Yilmaz, M.I.; Pekel, A.; Beyzadeoglu, M. (Experimental Oncology, 2006)
Aim: To investigate whether granulocyte-macrophage colony-stimulating factor (GM-CSF) with or without thalidomide can induce apoptosis and differentiation of HL-60 acute promyelocytic leukemia cell line in vitro. Methods: Effect of GM-CSF and thalidomide on proliferation of HL-60 cells was evaluated by MTT assay, cell cycle analysis was performed by propidium iodide staining approach and flow cytometry, and apoptosis rate was analyzed using FITC-conjugated annexin-V and FACScan flow cytometry. Results: The study revealed that thalidomide alone at high concentrations inhibited HL-60 cell growth and induced apoptosis. Three days treatment of low-dose thalidomide in combination with GM-CSF induced marked terminal differentiation of HL-60 cells, as it was assessed by increased expression of differentiation antigens on cell surface. Conclusion: Treatment of HL-60 cells by low concentration of thalidomide combined with GM-CSF induced terminal differentiation of HL60 cells in vitro, which may be advantageous for the elaboration of novel therapeutic regimens in patients with differentiation-inducible leukemias.